Description Of Blood Fever Baby In Bontobangun Public Health - Irmawati; Rusnawati (Jurnal Life Birth, 2018)
Dengue Hemorrhagic Fever (DHF) or Dengue Haemorrhagic Fever (DHF) is an acute disease, is endemic and can periodically cause Extraordinary Events (KLB).Based on data obtained from the Medical Record at the Bontobangun Community Health Center, Rilau Ale District, Bulukumba Regency, in 2014 there were 237 births and 17 babies were found to have dengue cases, and in 2015 there were 220 babies and 25 babies were found. dengue fever cases, and in January - March 2016 as many as 5 babies.The general objective of this study was to find out the incidence of dengue fever in infants at the Bontobangun Community Health Center, Rilau Ale District, Bulukumba Regency in 2016. The research design used in this study was a descriptive survey, the time and location of the study were carried out at the Bontobangun Public Health Center in Rilau Ale District, Bulukumba Regency in May. until June 2016. The sampling technique used in this study was total sampling or saturated sampling. The population in the study was infants with dengue cases in Bontobangun Public Health Center, Rilau Ale Subdistrict, Bulukumba Regency from 2015 as many as 25 people. and samples in this study were 25 infants who had dengue cases in Bontobangun Public Health Center, Rilau Ale District, Bulukumba Regency in 2015. The research instrument used in this study was a document from the medical record of the Bontobangun Public Health Center and data collection techniques in this study based on secondary data and processed manually. From the research that has been done, the results show that the highest incidence of dengue fever in infants is dengue fever with a mild criterion of 12 infants (48%) and the lowest in dengue fever with severe criteria of 3 infants (12,%) from 25 total baby samples. The incidence of dengue fever with inpatient criteria is 13 babies (52%) and criteria with outpatient care are 12 infants (48%) of 25 total baby samples.